Study protocol for a randomized controlled trial: Integrating the 'Time-limited Trial' in the emergency department. - Tadayuki Hashimoto; Rachel K Putman; Anthony F Massaro; Youkie Shiozawa; Katherine McGough; Kerry K McCabe; Judith A Linden; Wei Wang; Shan W Liu; Maura Kennedy; Thanh H Neville; Jacqueline M Kruser; et al. (PLoS ONE)
Introduction Time-limited trial (TLT) is a structured approach between clinicians and seriously ill patients or their surrogates to discuss patients' values and preferences, prognosis, and shared decision-making to use specific therapies for a prespecified period of time in the face of prognostic uncertainty. Some evidence exists that this approach may lead to more patient-centered care in the intensive care unit; however, it has never been evaluated in the emergency department (ED). The study protocol aims to assess the feasibility and acceptability of TLTs initiated in the ED. Methods and analysis We will conduct a parallel group, clinician-level, pilot randomized clinical trial among 40 ED clinicians. We will measure feasibility (e.g., the time it takes to conduct the TLTs by ED clinicians) and clinician and patient-reported acceptability of the TLT, and also track patients' clinical outcomes via medical record review. Discussion This study protocol will investigate the potential of TLT initiated in the ED to lead to patient-centered intensive care utilization. By doing so, the study intends to improve palliative care integration for seriously ill older adults in the ED and intensive care unit. Trial identifier and registry name ClinicalTrials.gov ID: NCT06378151 https://clinicaltrials.gov/study/NCT06378151; Pre-results; a randomized controlled trial: Time-limited Trials in the Emergency Department.